Hubungan Antara Tekanan Intraokular, Diabetes Mellitus, dan Hipertensi dengan Visus Setelah Operasi Fakoemulsifikasi - Veronica Lusiana Sinurat; Reinne Natali Christine; Tirsa Adella (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2022)
Introduction: The objective of this study is to determine whether there is a relationship between intraocular pressure (IOP), diabetes mellitus, and hypertension with visual acuity in senile cataract patients after phacoemulsification surgery. Methods: A retrospective cross-sectional study of senile cataract patients who underwent phacoemulsification surgery from 2019-2020 at Christian University of Indonesia General Hospital. Data were taken from medical records using purposive sampling, consist of visual acuity before and after phacoemulsification, visual acuity during 3 months of follow up, IOP before and after phacoemulsification, and the presence of systemic comorbidities such as hypertension and diabetes mellitus. Data were analyzed statistically with SPSS. Result: 122 eyes from 83 patients mostly had severe visual impairment before and a day after phacoemulsification, and improved to normal vision after a month and 3 months following phacoemulsification. The mean IOP was 18,36 mmHg and 21,33 mmHg before and after phacoemulsification. There were 78 patients who had systemic comorbidities such as hypertension and diabetes mellitus. There was no significant correlation between IOP and hypertension with visual acuity after phacoemulsification (p>0,005). Meanwhile, significant correlation was found between diabetes mellitus with visual acuity a day and a month after phacoemulsification (p<0,005). Conclusion: Diabetes mellitus has a significant relationship with visual acuity a day and a month after phacoemulsification surgery.